The Effect of Taxpayer Awareness, Tax Socialization and Tax Sanctions on Two-Wheeled Motor Vehicle Taxpayer Compliance in Pacitan Regency - Della Restiana,; Erna Chotidjah Suhatmi,; Indra Hastuti, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the effect of taxpayer awareness, tax socialization and tax sanctions on motor vehicle taxpayer compliance. The research method used is a quantitative method with primary data collection through questionnaires. The sample in this study was 100 respondents. The data analysis technique used was multiple linear regression analysis. The results of the study are that taxpayer awareness, tax socialization and sanctions have an effect on two-wheeled motor vehicle taxpayer compliance in Pacitan Regency. The results of the study are proven in the partial test (t-test) which shows that the significance value of the taxpayer awareness variable is 0.002, the tax socialization variable is 0.001 and the tax sanction variable is 0.001.